VASEKTOMI DAN TUBEKTOMI PERSPEKTIF MAQASID AL-SYARI’AH - Nastangin (MAHAKIM Journal of Islamic Family Law, 2019)
The Family Planning Program handled by the National Population and Family Planning Agency (BKKBN) is a form of human effort in order to overcome population problems through population control with the aim of creating a prosperous and happy family. In Indonesia, vasectomy and tubectomy is one of the contraceptives in the National Family Planning Program, considered the only safe method for family planning for men and women, can be trusted to limit offspring. Vasectomy is a family planning method for men through small surgery to cut and bind both sperm cell channels. Whereas tubectomy is sterilization for women, by cutting both the cell lines of the egg (tubal palupi) and closing them so that the egg cannot get out and the sperm cells cannot enter to meet the egg, so pregnancy does not occur. The purpose of this paper is to find out how vasectomy and tubectomy are in the perspective of Maqasid al-Syari’ah. This writing uses the Maqasid al-Syari’ah approach by explaining the nature and wisdom of its formal object. The conclusion of this paper is that limitation of offspring by vasectomy / tubectomy can be allowed in an emergency (emergency) with the aim of achieving benefit in accordance with the objectives of Islamic law (Maqasid al-Syari’ah), one of which is to protect the soul and offspring.